Soccer-specific video simulation for improving movement assessment - Cortes, N.; Blount, E.; Ringleb, S.; Onate, J. A. (Sports Biomechanics, 2011)
The improvement of ecological validity of laboratory research studies has recently come to the forefront of technology with virtual reality scenarios. The purpose of this study was to assess differences between unanticipated and anticipated lower extremity biomechanics while performing a sidestep cutting task. A visualization software was developed for this purpose, which would recreate a soccer game situation for use in a laboratory setting. Thirteen participants volunteered for this study. Lower extremity biomechanical data were collected with a VICON motion analysis system and two force plates, under anticipated and unanticipated conditions while performing a sidestep cutting task. Paired t-tests were conducted to assess possible differences between conditions. Alpha level was set a priori at 0.05. We found an increased knee adduction angle (unanticipated: -7.2 ± 5.3°; anticipated: -4.0 ± 5.3°), and knee internal rotation (unanticipated: 8.1 ± 4.7°; anticipated: 5.2 ± 6.5°) when performing the unanticipated condition (p < 0.05). The methodological approaches for studies investigating the factors possibly associated with ACL injury may need to take into account the laboratory environment and how the task(s) are presented to the participants.